On the democratic constant of Haar subsystems in $L_1[0,1]^d$ - Srapionyan, Nerses (National Academy of Sciences of Armenia)
In this paper, we estimate the democratic constant for the democratic subsystems of the $d$-dimensional Haar system in $L_1[0,1]^d$.
Keywords: Approximations and expansions; Functional analysis